2015
DOI: 10.1371/journal.pone.0131715
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Completed Suicide: a Meta-Analysis

Abstract: IntroductionSuicide is a major public health concern and a leading cause of death around the world. How religion influences the risk of completed suicide in different settings across the world requires clarification in order to best inform suicide prevention strategies.MethodsA meta-analysis using search results from Pubmed and Web of Science databases was conducted following PRISMA protocol and using the keywords “religion” or “religious” or “religiosity” or “spiritual” or “spirituality” plus “suicide” or “su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 43 publications
6
85
2
3
Order By: Relevance
“…About three-quarters of the studies published to-date, including studies in Western (predominantly Christian) and in Middle Eastern (predominantly Muslim) countries, have reported significant inverse relationships between at least one aspect of religion and at least one dimension of suicidality Stack and Kposowa 2011). A meta-analysis of international studies, including case-control and retrospective cohorts, found an overall protective effect of religiosity against suicide (Wu et al 2015).…”
Section: Religiosity and Suicidalitymentioning
confidence: 99%
“…About three-quarters of the studies published to-date, including studies in Western (predominantly Christian) and in Middle Eastern (predominantly Muslim) countries, have reported significant inverse relationships between at least one aspect of religion and at least one dimension of suicidality Stack and Kposowa 2011). A meta-analysis of international studies, including case-control and retrospective cohorts, found an overall protective effect of religiosity against suicide (Wu et al 2015).…”
Section: Religiosity and Suicidalitymentioning
confidence: 99%
“…Underlying these hypotheses were observations that religion potentially provides a set of coping mechanisms for responding to stress, religion can offer social support through participation in religious communities, some religions explicitly teach members not to commit suicide, and some religions teach members to limit or abstain from alcohol consumption (a risk factor for suicide). (Wu, Wang et al 2015)…”
Section: Introductionmentioning
confidence: 99%
“…In fact, level of religious involvement tends to be inversely related to depression, SB, drug misuse, impulsivity, and pathological gambling (Casey et al, 2011;Ronneberg et al, 2014;Caribé et al, 2012). With regard to SB, the studies entailed heterogeneous samples of patients presenting with several mental illnesses (Wu et al, 2015). However, what little research there is on patients with mood disorders suggests that religiosity bestows a protective effect against SB in this population (Mosqueiro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%